Semantic Similarity Analysis for Exam Questions Using Sentence Transformer Model - Shakya, Nischal; Shrestha, Milan; Subedi, Roshan; Swarnakar, Nitesh; Neupane, Upendra Prasad; Ghimire, Sharad Kumar (International Journal on Engineering Technology, 2025)
The aim is to explore the effectiveness of using the SBERT model and vector database for performing question similarity analysis. This involves building a vector database by training a sentence transformer model on a large corpus of text data. The vector dataset is then used to analyse question similarity by retrieving similar questions and similarity scores to a given search query. The model is trained on a large corpus of ALLNLI datasets, other paraphrase datasets such as MRPC and PAWS, and the semantic similarity of datasets such as STS, and finally adapted on 9,282 custom-prepared engineering datasets. The sentence transformer model is trained using the datasets mentioned above with MNR Loss as the loss function. The effectiveness of the model is evaluated by using the STS test dataset and test set of the MRPC. The results demonstrate that using a sentence transformer model and vector database for question similarity analysis outperforms the baseline method of keyword matching. The approach achieved a Spearman correlation value of 0.863 on the STS benchmark and an accuracy of 88.7% on the MRPC test. The Spearman correlation value in the SBERT paper for the NLI-large dataset was below 0.80. These values show that continuous training of the model on other datasets besides NLI helps to increase the performance and performs better for downstream tasks. This suggests that the use of the sentence transformer model and vector database is a promising approach for performing question similarity analysis, which could have significant implications for information retrieval systems.